Evaluation of the effects of a standardized aqueous extract of Phyllanthus emblica fruits on endothelial dysfunction, oxidative stress, systemic inflammation and lipid profile in subjects with metabolic syndrome: a randomised, double blind, placebo controlled clinical study - Pingali Usharani; Padma Latha Merugu; Chandrasekhar Nutalapati (BMC, 2019)
Abstract Background Endothelial dysfunction (ED) has been observed in individuals with metabolic syndrome (MetS) and contributes to the initiation and progression of atherosclerosis. The primary management of MetS involves lifestyle modifications and treatment of its individual components with drugs all of which have side effects. Thus, it would be of advantageous if natural products would be used as adjuncts or substitutes for conventional drugs. The aim of the present study was to evaluate the effect of standardized aqueous extract of fruits of Phyllanthus emblica (P. emblica) 250 mg and 500 mg twice daily on ED, oxidative stress, systemic inflammation and lipid profile in subjects with MetS. Methods In this randomised, double-blind, placebo-controlled clinical study endothelial function was measured by calculating reflection index (RI) using digital plethysmograph. Oxidative stress biomarkers used were nitric oxide (NO), glutathione (GSH) and malondialdehyde (MDA). Systemic inflammation was measured by determining high sensitivity C-reactive protein (hsCRP) and dyslipidemia by lipid profile. ANOVA, paired and unpaired t-test were used. P-value < 0.05 was considered statistically significant. Results Out of 65 screened subjects all 59 enrolled completed the study. P. emblica aqueous extract (PEE), 250 mg and 500 mg twice daily dosing, showed significant reduction in mean RI, measure of endothelial function, at 8 and 12 weeks (p <  0.001) compared to baseline and placebo. Significant mean % change was seen in oxidative stress biomarkers, NO (+ 41.89%, + 50.7%), GSH (+ 24.31%, + 53.22%) and MDA (− 21.02%, − 31.44%), and systemic inflammation biomarker, hsCRP (− 39.68%, − 53.77%) (p <  0.001) at 12 weeks with 250 mg and 500 mg twice daily dosage respectively. Significant mean % change was also seen at 12 weeks with TC (− 7.71%, − 11.11%), HDL-C (+ 7.33% + 22.16%, p <  0.05), LDL-C (− 11.39%, − 21.8%) and TG (− 9.81%, − 19.22%) respectively with 250 mg and 500 mg twice daily (p <  0.001). PEE 500 mg twice daily was significantly more efficacious than the 250 mg twice daily and placebo. No participant discontinued the study because of adverse events. Conclusions P.emblica aqueous extract significantly improved endothelial function, oxidative stress, systemic inflammation and lipid profile at both dosages tested, but especially at 500 mg twice daily. Thus, this product may be used as an adjunct to conventional therapy (lifestyle modification and pharmacological intervention) in the management of metabolic syndrome. Trial registration This study was registered with Clinical Trials Registry - India (CTRI) with the registration number of CTRI/2017/09/009606. The study was registered retrospectively on 4th September 2017.